Ethics and Economics: An Introduction to Free Markets, Equality and Happiness - Johan Graafland (Routledge, 2022)
This textbook applies economic ethics to evaluate the free market system and enables students to examine the impact of free markets using the three main ethical approaches: utilitarianism, principle-based ethics and virtue ethics. Ethics and Economics systematically links empirical research to these ethical questions, with a focus on the core topics of happiness, inequality and virtues. Each chapter offers a recommended further reading list. The final chapter provides a practical method for applying the different ethical approaches to morally evaluate an economic policy proposal and an example of the methodology being applied to a real-life policy. This book will give students a clear theoretical and methodological toolkit for analyzing the ethics of market policies, making it a valuable resource for courses on economic ethics and economic philosophy. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non-Commercial (CC-BY-NC) 4.0 license.
Keywords: 330; Good Life; Free Market Institutions; Violated; Virtue Ethics; Economic Freedom; Doux Commerce; Capitalistic Justice; Doux Commerce Thesis; Negatively Related; Confer; HDI; Free Market Perspective; Perfect Duties; Life Satisfaction; Economic Freedom Indicators; Fraser Institute; Negative Rights; Care Ethics; Flat Tax System; Free Market System; Sum Ranking; Societal Happiness; Deontological Ethical Theory; Keynes; Average Income